Incorporation of 3-Aminobenzanthrone into 2′-Deoxyoligonucleotides and Its Impact on Duplex Stability - Mark Lukin; Tanya Zaliznyak; Francis Johnson; Carlos R. de los Santos (Journal of Nucleic Acids)
3-Nitrobenzanthrone (3NBA), an environmental pollutant and potent mutagen, causes DNA damage via the reaction of its metabolically activated form with the exocyclic amino groups of purines and the C-8 position of guanine. The present work describes a synthetic approach to the preparation of oligomeric 2′-deoxyribonucleotides containing a 2-(2′-deoxyguanosin-N2-yl)-3-aminobenzanthrone moiety, one of the major DNA adducts found in tissues of living organisms exposed to 3NBA. The NMR spectra indicate that the damaged oligodeoxyribonucleotide is capable of forming a regular double helical structure with the polyaromatic moiety assuming a single conformation at room temperature; the spectra suggest that the 3ABA moiety resides in the duplex minor groove pointing toward the 5′-end of the modified strand. Thermodynamic studies show that the dG(N2)-3ABA lesion has a stabilizing effect on the damaged duplex, a fact that correlates well with the long persistence of this damage in living organisms.